Removal of zinc from rubber thread manufacturing industry wastewater using chemical precipitant/flocculant - Subbiah, R.M.; Sastry, C.A.; Agamuthu, Pariatamby (2000)
Wastewater from the rubber thread manufacturing industry is acidic in nature with PH in the range of 3.8 to 4.4 and containing high concentrations of COD, BOD, Total-N and zinc. The high BOD and COD ratio of the wastewater (0.78 to 0.90) indicates that the rubber wastewater is biodegradable and can be treated effectively by an anaerobic digestion process commonly employed in this industry. However, because the wastewater contained high concentrations of zinc, 250 to 310 mg/L, which could inhibit the digestion process, it was pretreated by chemical precipitation/flocculation. A treatment process using a combination of sodium sulfide and polyelectrolyte LT 27 at concentrations of 800 and 5 mg/L, respectively, is the most cost-effective system for zinc removal from the wastewater Zinc removal by sodium sulfide is not affected by pH. The optimum settling time was 60 min, whereas the optimum flocculation time was 20 min, and a speed of 20 rpm in a 110 mm diameter reactor gave the best res The estimated cost of zinc removal using this method was RM1.04/m(3) (US $0.26/m(3)) of wastewater discharged.